Aksi Bergizi: Health Promotion Program Supporting Healthy Eating Habits in School Children - Fitriyani, Meidina; El Hayatli, Miftahurrahmah; Muflih Faadhilah; Lestari, Puji; Kristina (BKM Public Health and Community Medicine, 2024)
Purpose: The Aksi Bergizi program aims to cultivate a school community that values healthy, clean, and nutritious food. Its specific objectives include promoting health-oriented policies in schools related to healthy eating habits, creating a supportive environment for healthy eating among school children by establishing Agents of Change (AoC) for the Healthy Eating Movement for School Children (GEMASS), enhancing the capacity and skills of teachers, staff, students, and parents regarding healthy eating habits, and building networks with relevant stakeholders (Puskesmas, BPOM, School Committee) to support healthy eating in schools. Methods: Children spend about a quarter of their time in school daily, often consuming snacks whose nutritional content and cleanliness are unknown, potentially affecting their health. Preventive actions against the adverse effects of unhealthy snacks are necessary. The Aksi Bergizi program addresses the problem of unhealthy food consumption among school children. The program was implemented at SDN Percobaan 2 Yogyakarta, forming a team of AoC GEMASS to supervise, control, and educate the school community about healthy eating habits. The AoC GEMASS team includes students, teachers, the school committee, and parents. Additionally, the program promotes the policy of "No Snacking Fridays" as a flagship initiative. Results: The Aksi Bergizi program established the AoC GEMASS team to monitor and educate the school community on healthy eating practices. This team consists of students, teachers, the school committee, and parents. The program also strengthened the policy of "No Snacking Fridays," a key initiative of the school. Through these efforts, the program aims to create a healthy and nutritious school environment and build networks with stakeholders to support healthy eating in schools. Conclusion: The Aksi Bergizi program effectively promotes healthy eating habits among school children by establishing a supportive environment and engaging the school community and stakeholders. The initiative fosters a healthier school environment and encourages collaboration to sustain healthy eating practices.